PEREMPUAN DALAM POLITIK MASKULIN - Listyani (Al'Adalah, 2014)
The idea of action affirmatif always coloring discourse of political participation of women in indonesia. It is meaningful that problem of political participation of women in indonesia is still viewed as something that should be championed. With megawati his seat to become president and increasing of the number of women legislators haven 't viewed as describing indonesian women success in politics. Even if compared to the united states, indonesian women have political right early.The emergence of the people of representatives among women is pointed out in parliament is not yet emerge women as decision making. It is not surprising if political social life in Indonesia are still seen male perspecive. The involvement of women in public spaces and are strategic spaces decision-making is the only way to prevent the interests of women represented . The position of women in the Parliament is allowing women to conceive even transforms to a policy that is created by the legislature to be gender friendly. When the involvement of women in taking strategic decisions has been in an ideal position, expected residents of Indonesia women who account for 50% of his interests can be guaranteed.